1991
DOI: 10.1111/j.2044-8295.1991.tb02379.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of testosterone on human aggression

Abstract: Animal studies show clear evidence for a causal link between testosterone and aggression. This review assesses studies involving androgens, principally testosterone, and human aggression. Evidence for a possible effect of prenatal androgens is inconclusive. In adults, higher testosterone levels are found in groups selected for high levels of aggressiveness. Correlations between testosterone and aggression were low when hostility inventories were used, but higher (r = .38) when aggressiveness was rated by other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
210
1
18

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 479 publications
(240 citation statements)
references
References 106 publications
11
210
1
18
Order By: Relevance
“…Extensive evidence indicates that T is correlated with dominant behaviors aimed at asserting one's social status, often in the form of physical or non-physical aggression (Archer, 1991(Archer, , 2006Mazur and Booth, 1998;Book et al, 2001). In the context of the ultimatum game, the rejection of an unequal offer favoring the proposer has been interpreted as a form of non-physical aggression in response to social provocation (Burnham, 2007;Mehta and Beer, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive evidence indicates that T is correlated with dominant behaviors aimed at asserting one's social status, often in the form of physical or non-physical aggression (Archer, 1991(Archer, , 2006Mazur and Booth, 1998;Book et al, 2001). In the context of the ultimatum game, the rejection of an unequal offer favoring the proposer has been interpreted as a form of non-physical aggression in response to social provocation (Burnham, 2007;Mehta and Beer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found significant correlations between circulating T and various forms of dominant or aggressive behavior (Archer, 1991(Archer, , 2006Mazur and Booth, 1998;Book et al, 2001;Eisenegger et al, 2011;van Honk et al, 2014). One possibility is that high basal T, rather than variations in its circulating level, is a biological marker of stable individual differences in personality (Sellers et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of testosterone, previous research has mostly focused on aggression and dominance, with several reviews and metaanalyses providing evidence for a weak but positive relationship between testosterone and various forms of aggressive or antisocial behavior (Archer, 1991(Archer, , 2006Book, Starzyk, & Quinsey, 2001;Yildirim & Derksen, 2012). However, testosterone has also been investigated in the context of positive social behavior, such as cooperation, affiliation, empathy, and prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%